Incidence of Second Malignancy in Patients with Papillary Thyroid Cancer from Surveillance, Epidemiology, and End Results 13 Dataset. (26th June 2018) - Endo, Mayumi; Liu, Jessica B.; Dougan, Marcelle; Lee, Jennifer S.
Abstract : Increased risk of second primary malignancy (SPM) in papillary thyroid cancer (PTC) has been reported. Here, we present the most updated incidence rates of second primary malignancy from original diagnosis of PTC by using the data from the Surveillance, Epidemiology, and End Results. In this cohort, 3, 200 patients developed SPM, a substantially higher number than in the reference population of 2, 749 with observed to expected ratio (O/E) of 1.16 (95% CI; 1.12–1.21). Bone and joint cancer had the highest O/E ratio of 4.26 (95% confidence interval [CI] 2.33–7.15) followed by salivary gland (O/E 4.15; 95% CI 2.76–6.0) and acute lymphocytic leukemia (O/E 3.98; 95% CI 2.12–6.8). Mean age at the diagnosis of SPM was 64.4 years old. Interestingly, incidence of colorectal cancer was lower in thyroid cancer survivors compared to general population (large intestine O/E 0.3; 95% CI 0.06–0.88, rectum O/E 0.6; 95% CI 0.41–0.85); however, this was not observed in patients who underwent radiation therapy. The incidence of SPM at all sites was higher during 2000–2012 compared to 1992–1999 (O/E 1.24 versus 1.10). Surprisingly, patients with micropapillary cancer had higher incidence of SPM than counterparts with a larger tumor in radiation group (O/E of 1.40 versus 1.15). O/E of all cancers were higher in males compared to females with O/E of 1.41 versus 1.17 during the period of 2000–2012. Diagnosis of PTC before age 50, especially at age 30–34, was associated with higher incidence of overall SPM (age 30–34; O/E 1.43; 95% CI; 1.19–1.71). Efficient monitoring strategies that include age at the time of thyroid cancer diagnosis, exposure to radiation, gender, and genetic susceptibility may successfully detect SPM earlier in the disease course. This is especially important given the excellent prognosis of the initial thyroid cancer itself.